URGENSI PENGIMPLEMENTASIAN NILAI-NILAI SYARIAT ISLAM DALAM KEHIDUPAN NARAPIDANA DI LEMBAGA PEMASYARAKATAN ACEH - Rahmatillah, Syarifah (Al-Ijtima`i: International Journal of Government and Social Science, 2018)
The study discusses the efforts to find solutions in realizing quality prisoner formation in the Ministry of Law and Human Rights in accordance with the values ​​of Islamic law. In particular, this study looked at the conditions of the formation of prisoners in detention centers and prisons which had been carried out by the Aceh Province of Law and Human Rights Ministry through the concept of Islamic law and wanted to know what actions were taken by the Penitentiary if the prisoners conducted jarimah as stipulated in Qanun No. 6 of 2014 concerning Jinayat Law. The author used descriptive analysis research methods with the data collection techniques were interview and documentation review. This research was carried out at institutions that are directly related to prisoner guidance systems, namely the Sigli Detention Center and Meulaboh Prison. The results showed that, in the Sigli and Meulaboh Prison detention centers which were the samples of this study, the guiding system of prisoners at the Meulaboh Penitentiary and Sigli Prison refers to Law No. 12 of 1995 concerning Correctional Services. The meaning of the system of religious guidance for prisoners and detainees is still very standard, which is about routine activities, namely attending lectures, meeting together, praying in congregation. While their understanding of the existence of the Shari'a Qanun is inadequate. So, if there were cases such as gambling and abuse of narcotics and other crimes, sanctions applied were only sanctions for reprimand or only limited to using positive law in accordance with the Criminal Code and other Special Criminal Law rules.